2020
DOI: 10.1021/acs.jpclett.9b03470
|View full text |Cite
|
Sign up to set email alerts
|

N–H Chirality in Folded Peptide LK7β Is Governed by the Cα–H Chirality

Abstract: Recent chiral sum-frequency generation vibrational spectroscopy (cSFG-VS) measurements revealed that the two N-H stretching modes in the 3000-3500 cm-1 range in folded protein and peptide exhibit chiral characteristics. Here we report the first phase-resolved sub-wavenumber high-resolution broadband SFG-VS (HR-BB-SFG-VS) measurement of the LK 7 β peptide. The results show that this chiral N-H band consists of four, instead of two, distinctive peaks, and they are with two groups of opposite spectral phases. Mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…We also identified two peptide N-H stretching bands with an opposite phase at 3,247 and 3,270 cm −1 (Fig. 2A), consistent with a prior report (12), and two peptide N-D stretching bands with an opposite phase at 2,391 and 2,445 cm −1 (Fig. 2C).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We also identified two peptide N-H stretching bands with an opposite phase at 3,247 and 3,270 cm −1 (Fig. 2A), consistent with a prior report (12), and two peptide N-D stretching bands with an opposite phase at 2,391 and 2,445 cm −1 (Fig. 2C).…”
Section: Discussionsupporting
confidence: 91%
“…2C). To explain the opposite phases of the two N-H stretching bands, Hu et al (12) proposed that adjacent backbone nitrogen atoms along the β-strand are chiral centers with opposite handedness (i.e., pro-S and pro-R). This proposal would require a substantial sp 3 -hybridized character of the nitrogen atoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). It was also confirmed that mirror-image β-sheet assemblies of LK 7 β exhibit opposite orientations in both C-H and N-H modes, as they should since they are each other's chiral enantiomer (9). With this advancement a further question about the chirality of biomolecules and the hydration shell can now be answered: Do left-or right-handed chiral water superstructures exist around peptides?…”
mentioning
confidence: 81%